Feminism and animalism: identifying the roots of oppression (Balthazar, 2021)
This paper critically examines some of the first feminist theories, aiming to show how the recognition of discrimination and violence towards every living being can be a very useful tool to deal with problems related to sex and gender. Some feminist themes will be reinterpreted on the basis of theories that take into consideration the totality of living beings in order to highlight the moments some inconsistencies. More specifically, starting from the revolution of the concept of the subject that originates from Darwinian thought, it will be noted that some theoretical assumptions of formulations aimed at contrasting gender discrimination still involve the re-proposition of hierarchising categorisations and exclusions. Introducing the work of Carol Adams, it is pointed out that these assumptions can be traced back to the concepts of otherness and somatophobia: without disregarding the body and the biography of each living being, the author identifies in these two principles the constitutive traits of relationships marked by domination. Therefore she proposes to rethink discrimination issues in a unitary way.
Keywords: discrimination; violence legitimisation; feminism; animalism